Analysis of Representation of Nature and its Meaning in the Asyik Dance through Aristotle’s Theory of Mimesis - Jelly, Ratna Fazlinda; Pisali, Amsalib; Tengku Anuar, Tengku Fauzan; Zainal, Sharifuddin; Ishak, Ismaliza; Muka, Adinda Usin (Environment-Behaviour Proceedings Journal, 2025)
The Tarian Asyik, a royal dance from Kelantan originating in the Pattani Kingdom of Southern Thailand, was created by Raja Kuning, the Queen of Pattani, to express longing for a lost bird. Beyond court entertainment, the Asyik Dance represents nature through graceful movements, symbolic imagery, and harmony with the natural world. This study examines these representations by analysing three motifs—the bird, ocean waves, and elephant—through Aristotle’s theory of mimesis, which interprets art as the imitation of life. The findings reveal that Tarian Asyik embodies aesthetic beauty, philosophical meaning, and the Malay worldview.